Análisis del tratamiento informativo de la agencia EFE sobre la incursión ecuatoriana a la Embajada de México en Quito, de diciembre del 2023 a mayo del 2024 - Cevallos Hernández, Michelle Stephanie (2025)
This research work presents an analysis of the informative treatment that the international news agency EFE provided in the case of the Ecuadorian invasion of the Mexican embassy in Quito, covering the period from December 2023 to May 2024. The general objective of the research was to analyze the notes on the subject found in the established period. The notes cover the period before, during, and after the conflict, considering any news that has a direct or indirect relationship with the central theme, which allows for a broader analysis of the theme. A qualitative methodology was used, where the content analysis technique was used, which allowed to have three matrices as tools, the structural analysis matrix where essential elements of the note are detailed, in the second matrix called discourse analysis it was known how the rhetorical strategies were handled in each of the notes, The last matrix was based on a semiotic analysis, where the main subjects were identified and how their narrative was constructed. For a broader view of the theme, interviews were conducted with people from the EFE Agency from each of the two parties involved. To gain a broader understanding of the theme, interviews were conducted with representatives from the EFE Agency and each of the two parties involved, including the representative from EFE Ecuador and the editor-in-chief of EFE Mexico. The results obtained showed that the EFE Agency complied with most of the characteristics of the news to present the information. However, in some it lacked a certain contrast, which evidenced an inclination towards one of those involved, which are Mexico, Ecuador, and Jorge Glas. Based on these three positions, it was reflected that there was an involuntary media bias in favor mainly of Mexico. This bias toward Mexico was reflected in the narrative of the news found, even though they met the criteria for news. Considering external factors such as the information that the respective governments provided to the media, and internal factors such as the lack of communication that existed between the EFE Mexico department and EFE Ecuador, it was concluded that these were the main reasons that influenced this media bias, which, despite the agency's attempt to maintain objectivity, could be seen in several notes, where media bias is evidente